Determination of trauma severity level by means of the injury severity score - Gennari, Terezinha Dalossi (1995)
The severity of traumas in hospitalized patients was characterized by means of the Injury Severity Score (ISS) was studied prospectively. One hundred trauma patients hospitalized in a trauma referral health facility located in S. Paulo, Brazil, were analyzed. Of the total number of patients, 68 had blunt trauma and 32 penetrating trauma. As to ISS, it was discovered that 53.0% of the blunt trauma patients had mild trauma (ISS 1-15), 29,4% moderate trauma (ISS 16-24), and 17.6% showed severe trauma (ISS 25); 34.4% of the penetrating trauma patients had mild trauma, 18.7% moderate trauma and 46.9% severe trauma. The mean and standard deviations relationg to the ISS of blut and penetrating trauma patients were, respectively, 14.9 ± 8.1 and 20.8 ± 11.0; the respective mortality rates were of 11.8% and 12.5%